Homalomeneae (Araceae) of Borneo XXVIII– Homalomena bengohensis [Chamaecladon Clade] a new species endemic to the Bengoh Range, Sarawak - Wong, Sin Yeng; Peter C., Boyce (Firenze University Press, 2023)
A new species of Homalomena Chamaecladon Clade is described from the Bengoh Range, Kuching Division, Sarawak, and compared with the two most similar described species from Kuching: H. paucinervia from the Matang Massif, and H. santubongensis from Gunung Santubong. The three species are illustrated from living plants and differentiated in an identification key.